2021
DOI: 10.2147/idr.s333818
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Next-Generation Sequencing for Pulmonary Fungal Infection Diagnosis: Lung Biopsy versus Bronchoalveolar Lavage Fluid

Abstract: Purpose: Metagenomic next-generation sequencing (mNGS) is widely used for pulmonary infection; nonetheless, the experience from its clinical use in diagnosing pulmonary fungal infections is sparse. This study aimed to compare mNGS results from lung biopsy and bronchoalveolar lavage fluid (BALF) and determine their clinical diagnostic efficacy. Patients and Methods: A total of 106 patients with suspected pulmonary fungal infection from May 2018 to January 2020 were included in this retrospective study. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 19 publications
4
27
0
Order By: Relevance
“…Yang et al. ( Yang et al., 2021 ) observed that mNGS (lung biopsy, bronchoalveolar lavage fluid [BALF]) had a significantly higher sensitivity than conventional tests for diagnosing pulmonary fungal infections. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al. ( Yang et al., 2021 ) observed that mNGS (lung biopsy, bronchoalveolar lavage fluid [BALF]) had a significantly higher sensitivity than conventional tests for diagnosing pulmonary fungal infections. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies on the detection of pulmonary infections using mNGS have focused on pathogens. Yang et al (Yang et al, 2021) observed that mNGS (lung biopsy, bronchoalveolar lavage fluid [BALF]) had a significantly higher sensitivity than conventional tests for diagnosing pulmonary fungal infections. Liu et al (Liu et al, 2021) evaluated the performance of BALF-mNGS in differentiating colonization and infection with Pneumocystis jirovecii and suggested that the fungal load differed significantly between the two groups (P. jirovecii pneumonia and P. jirovecii colonization).…”
Section: Introductionmentioning
confidence: 99%
“…As study has demonstrated that mNGS of lung tissue and bronchoalveolar lavage fluid could help diagnose fungal infection in lungs. 15 Thus, mNGS plays a more important role in FN patients, especially in the diagnosis of fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS is a high-throughput technology that provides direct information about the type of infection, without relying on microbial cultures ( 12 ). Considering the rapid speed and high sensitivity of mNGS, this technology may facilitate the timely diagnosis of disease, especially in life-threatening scenarios.…”
Section: Discussionmentioning
confidence: 99%